Investigate the Dosimetric and Potential Clinical Benefits Utilizing Stereotactic Body Radiation Therapy With Simultaneous Integrated Boost Technique for Locally Advanced Pancreatic Cancer: A Comparison Between Photon and Proton Beam Therapy - Liu, Peilin; Gao, Xian-shu; Wang, Zishen; Li, Xiaomei; Cao, Xi; Jia, Chenghao; Xie, Mu; Lyu, Feng; Shang, Shiyu; Ding, Xuanfeng (Frontiers in Oncology, 2021)
Purpose: To investigate the potential clinical benefits of using stereotactic body radiation therapy (SBRT) with simultaneous integrated boost (SIB) technique for locally advanced pancreatic cancer (LAPC) among different treatment modalities and planning strategies, including photon and proton. Method: Nineteen patients were retrospectively selected in this study. Thirteen cases with tumor located in the head of the pancreas and six cases with the tumor in the body of the pancreas. SBRT-SIB plans were generated using volumetric modulated arc therapy (VMAT), 2-field Intensity Modulated Proton Therapy (IMPT), and 3-field IMPT. The IMPT used the robust optimization parameters of ± 3.5% range and 5 mm setup uncertainties. Root-mean-square deviation dose (RMSD) volume histograms were used to evaluate the target coverage robustness quantitatively. Dosimetric metrics based on the dose-volume histogram (DVH), homogeneity index (HI), and normal tissue complication probability (NTCP) were analyzed to evaluate the potential clinical benefits among different planning groups. Results: With a similar CTV and SIB coverage, 2-field IMPT provided a lower maximum dose for stomach (median:18.6GyE, p<0.05), duodenum (median:32.62GyE, p<0.05) when the target was located in the head of the pancreas compared to VMAT and 3-field IMPT. The risks of ulceration or perforation (3.42%) and grade ≥3 GI toxicity (4.55%) were also decreased. However, for the target in the body of the pancreas, VMAT showed a lower maximum dose for the stomach (median 30.93GyE, p<0.05) and toxicity of ulceration or perforation (median:8.67%, p<0.05) compared to 2-field IMPT and 3-field IMPT, while other maximum doses and NTCPs were similar. The RMSD volume histogram (RVH) analysis shows 3-field IMPT provided better robustness for targets but not for OARs. Instead, 3-field IMPT increased the Dmean of organs such as the stomach, duodenum, and intestine. Conclusion: The results indicated that the tumor locations could play a critical role in determining clinical benefits among different treatment modalities. Two-field IMPT could be a better option for LAPC patients whose tumors are located in the head of the pancreas. It provides lower severe toxicity for the stomach and duodenum. Nevertheless, VMAT is preferred for the body with better protection for the possibility of ulceration or perforation.